الاطار القانوني لممارسة حرية التظاهر السلمي في الجزئر بين الضمانات القانونية و سلطة الضبط الاداري - عمير, سعاد; ناجي, حكيمة (University of Eloued جامعة الوادي, 2022)
إن ممارسة الحريات العامة دون ضوابط من شأنه أن يخلق فوضى، و اطلاق ممارستها يمكن أن يعيق حرية الجميع، و بالإطلاع على الضمانات الموضوعة في الدستور لضمان ممارسة الحريات العامة نجدها نسبية خاصة إذا تعلق الأمر بأحكام المادة 34 من التعديل الدستوري لسنة 2020 . و من هنا يتضح الهدف من هذه الدراسة ، بين نص دستوري يؤمن و يضمن ممارسة حرية التظاهر السلمي و بين نصوص قد تقيد أو تلغي هذه الحرية بدافع الحفاظ على النظام العام. وقد وصلنا إلى نتيجة مقتضاها أن حرية التظاهر السلمي عرفت تقليصا متدرجا في النظام القانوني الجزائري، في الوقت الذي كان ينتظر أن ينص الدستور و جملة القوانين المنظمة لممارسة هذه الحرية على ضمانات فاعلة لممارسة حرية التظاهر السلمي. The exercise of public freedoms without controls would create chaos, and launching their exercise could impede the freedom of everyone, and by looking at the guarantees established in the constitution to ensure the exercise of public freedoms, we find them relative, especially when it comes to the provisions of Article 34 of the constitutional amendment for the year 2020. Hence, the aim of this study is clear, between a constitutional text that secures and guarantees the exercise of the freedom of peaceful demonstration, and between texts that may restrict or cancel this freedom in order to preserve public order. We have come to the conclusion that the freedom of peaceful demonstration has witnessed a gradual reduction in the Algerian legal system, at a time when the constitution and the laws regulating the exercise of this freedom were expected to provide effective guarantees for the exercise of the freedom of peaceful demonstration.
The legal framework for the exercise of freedom of peaceful demonstration in Algeria between legal guarantees and the authority of administrative control
مقال
Keywords: التظاهر ; السلمي ; التقييد ; الحرية ; الممارسة; demonstration ; peaceful ; restriction ; freedom; practice